Subjective question generation and answer evaluation using NLP - Swapno, Ahmed Symum; Hamid, Mohammad Rafid; Shaheer, Safwan; Nur, Yaseen (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.